Pengaruh Strategi Polya terhadap hasil belajar penyelesaian soal cerita pecahan dalam masalah perbandingan dan skala di kelas V SD gugus X kecamatan koto tangah kota padang - hasan, Nurhasni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research is motivated by the use of inappropriate learning strategies in the learning of fraction story problems in the problem of comparison and scale that results in low student learning outcomes. This study aims to determine the effect of Polya Strategy on Learning Outcomes in Solving Fraction Story Problems in Comparative and Scale Problems in Class V SD of Cluster X in Koto Tangah District, Padang City. This type of research is quantitative in the form of quasy experiment design. The design used by the nonequivalent posttest-only control group design. The study was conducted at SDN 15 Padang Sarai, Padang City. Based on the results of the posttest obtained the average learning outcomes of solving story problems in control class students who apply conventional learning is 53.9. And the average value of learning outcomes in solving the story questions for the experimental class students by applying the Polya strategy is 72.4. Based on the results of hypothesis testing using the t-test on the real level α = 0.05 obtained t_count = 2.84 and ttable = 1.997, so that t_count> t table then Ha in this study was accepted and rejected H0. It can be concluded that Polya's strategy influences learning outcomes in solving fractional story problems in terms of comparison and scale in class V SD gugus X Kecataman Koto Tangah city of Padang.